Kompetensi Aparat Pengawas dalam Peningkatan Kinerja Pada Inspektorat Provinsi Sulawesi Utara - Sendoh, M. M.; Lumolos, Johny (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract. The purpose of this research is to assess the competence of regulatory authorities in improving performance in North Sulawesi Province Inspectorate. In this research, using qualitative methods. Data collected through interviews, observation and documentation of the 20 informants, 9 employees who have the education and supervision of 11 technical employees who have not been following the technical education supervision. Data were analyzed as categorical and diinterprestasi narrative. The results show the ability of supervisors have different technical performance, where that has followed the technical education quality supervision over the performance of the examination and have self- confidence, mastering the rules of supervision, able to work with other employees and enjoys a supervisory job responsibilities. Any employees who perform duties in the working units need continuous supervision of technical training, and for employees who have not followed the supervision of technical education may be given the opportunity to attend technical education supervision conducted by the local government and central government.Key words: Control, Competence, Performance